Visual preference of tourism destinations in the state of Pahang, Malaysia - Ani, Anisa; Mohamed, Noorizan; Ina Krisantia, (2012)
Visual preferences for various landscapes have been long standing interest to researchers. This research intends to understand what reflects the preferences through the respondent’s knowledge on the function and experience of the selected tourism scenes. Respondents selected according to their knowledge of the selected tourism destinations regardless their nationality. From the photos gathered during the site survey, a final set of ten most preferred scenes by the respondents were finalized to be used in the study. It was found that respondent’s familiarity has become the contributing factor in influencing the most preferred scenes. The results point that highland landscapes were most preferred by the respondents regardless their origins ; mostly influenced by their perception on natural environment protection and the calmness feeling provided by the selected highland scenes.